2002
DOI: 10.1097/00005176-200205000-00010
|View full text |Cite
|
Sign up to set email alerts
|

Trophic Effect of Multiple Growth Factors in Amniotic Fluid or Human Milk on Cultured Human Fetal Small Intestinal Cells

Abstract: In aminiotic fluid and in human milk, EGF, IGF-1, FGF, HGF, and TGF-alpha have a strong trophic effect on immature intestinal cells and may be involved in perinatal gastrointestinal adaptation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
93
0
6

Year Published

2002
2002
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 142 publications
(102 citation statements)
references
References 19 publications
3
93
0
6
Order By: Relevance
“…17 Trophic effects of AF have further been demonstrated on cultured human fetal small intestinal cells. 18 These studies suggest that growth factors found in AF, comparable to those in human milk, play a role in fetal growth and development. These trophic mediators are discussed below.…”
Section: Nutritive Functions Of Afmentioning
confidence: 96%
See 1 more Smart Citation
“…17 Trophic effects of AF have further been demonstrated on cultured human fetal small intestinal cells. 18 These studies suggest that growth factors found in AF, comparable to those in human milk, play a role in fetal growth and development. These trophic mediators are discussed below.…”
Section: Nutritive Functions Of Afmentioning
confidence: 96%
“…Recombinant TGF-a elicits a synergistic trophic response on cultured intestinal cells when combined with recombinant EGF, insulin-like growth factor-1, fibroblastic growth factor, and hepatocyte growth factor, but the trophic response is not as strong as either AF or breast milk. 18 The amnion cells of the umbilical cord express EGF, TGF-a, and the functional EGF/TGF-a receptor suggesting the possibility of a regulating role of the amnion in fetal growth and development. EGF and TGF-a have also been shown to stimulate the production of surfactant components.…”
Section: Nutritive Functions Of Afmentioning
confidence: 99%
“…Exogenous infusion of EGF in utero has been shown to accelerate the maturation of intestine enzyme activity as well as stimulate intestinal growth [22]. Interestingly, the salivary level of EGF is directly proportional to the gestational age of the infant [23]. Hepatocyte Growth Factor (HGF) and Vascular Endothelial Growth Factor (VEGF) are expressed in gut tissues and play a major role in the mucosal growth and repair [24].…”
Section: Physiology Of Gut Maturationmentioning
confidence: 99%
“…For studies of human milk-derived bioactives, the small intestinal FHs 74 Int. cell line has been widely used as a model (Ichiba et al, 1992;Kawamura et al, 1994;Wagner et al, 1998;Hirai et al, 2002;Takeda et al, 2004). We have shown that these small intestinal cells represent a very sensitive model for milk-derived bioactives (Purup et al, 2007).…”
Section: Cell-based Models Of the Gastrointestinal Tractmentioning
confidence: 99%